Extreme Low-Temperature Stress Affects Nutritional Quality of Amino Acids in Rice - Kang, Min; Liu, Gurong; Zeng, Yaowen; Zhou, Jia; Shi, Jiangyi; Tang, Liang; Liu, Leilei; Cao, Weixing; Zhu, Yan; Liu, Bing (Frontiers in Plant Science, 2022)
Global climate change has increased the frequency of extreme climate events, and their effects on the nutritional quality, especially on amino acids in rice, have not been quantified. With 3-year low-temperature stress (LTS) experiments including two rice varieties (Huaidao 5 and Nanjing 46), seven minimum/maximum temperature levels (one optimal 21/27 ℃ and six LTS levels from 17/23 ℃ to 6/12 ℃), and three LTS durations (3, 6, and 9 days) after flowering, we noted significant interactive effects of LTS at different stages, durations, and temperature levels on the content and accumulation of amino acids. LTS increased rice amino acid content, while decreasing its accumulation, with higher sensitivities to LTS at the flowering stage than at the grain filling stage. In most treatments, the lysine (the first limiting amino acid) and phenylalanine content increased under LTS at early and peak flowering stages but decreased at the grain filling stage in both varieties, and only leucine content increased at all three stages after flowering, while the content of other essential amino acids differed among the two varieties. With a 1 ℃·d increase in accumulated cold degree days, the relative content of essential amino acids increased by 0.01–0.41%, depending on the rice variety and growth stage. These results provide critical insights for assessing the potential impact of extreme climates on the nutrient quality of rice under future climate change.